Sponge (Porifera) fauna of Frobisher Bay, Baffin Island, Canada with the description of an Iophon rich sponge garden - Dinn, Curtis; Edinger, Evan; Leys, Sally P. (Zootaxa, 2019)
The deep-water sponge fauna of the Canadian Arctic remains to be fully described, particularly in areas that are not sampled by fisheries stock-assessment trawl surveys such as the major bays and fjords of the northern Labrador Sea and Baffin Bay. Frobisher Bay is a large inlet located on the southeast of Baffin Island. We used a remotely operated vehicle, as well as box cores and Agassiz trawls to study the sponge fauna of this bay. Over three years, from 2015 to 2017, sponge specimens were collected representing 24 distinct sponge taxa. Dense gardens of Iophon koltuni Morozov, Sabirov, & Zimina, 2019 were discovered at a site near Hill Island in inner Frobisher Bay. The species has a unique finger-like growth form and provides complex habitat in the inner bay. Other sponge species are new to the Northern Labrador marine ecoregion. In particular, we report geographic range extensions of Tetilla sibirica (Fristedt, 1887) and Craniella polyura (Schmidt, 1870), and provide spicule measurements and descriptions of Iophon piceum (Vosmaer, 1882) and Mycale lingua (Bowerbank, 1866). These species identifications, geographic range extensions, and an expanded description of a species synonym represent the first inventory of the sponge fauna of Frobisher Bay.